Validity of Electronic Signature on Deed of Sale and Purchase Agreement - Evita Isretno Israhadi (Universitas Dharma Wacana, 2022)
The development of technology today is increasingly advanced and sophisticated. Many changes have occurred, one of which is the number of transactions carried out via the internet. Therefore, electronic signatures or digital signatures that are made electronically based on asymmetric cryptography technology and have the same function as ordinary signatures on ordinary paper documents. Regarding evidence in court, there are several differences of opinion regarding the evidentiary power of electronically signed electronic documents. Electronic documents that have been electronically signed have the same evidentiary power as authentic deeds made by authorized officials, but differences of opinion arise from the notary. It is considered that it does not meet the requirements as an authentic deed, namely not facing directly to the authorized official. The legal power of electronic signatures needs to be further analyzed in the event of a dispute between the parties to an electronic agreement and the position of electronic signatures can or cannot be equated with conventional signatures. This research uses normative juridical method with statutory approach and conceptual approach. The resulting conclusion is that the validity of electronic signatures in the deed of sale and purchase agreement has not been recognized by the Electronic Information and Transaction Law.